Peer Review Regulation in the German Science and Research Association - E. Vodyanitskaya (Vestnik MGIMO-Universiteta)
The article describes peer review procedures used by the German Science and Research Association. It gives thorough analysis of the stages of peer review and provides a number of critical comments to the procedure regarding provision of additional information to grant applicants, increased reimbursement of the reviewers, reveal of information about the reviewers.